Does the classroom context moderate the effects of internalizing problems and peer status on peer victimization? Testing a vulnerability-by-context model - Garandeau, Claire; Malamut, Sarah; Laninga-Wijnen, Lydia; Salmivalli, Christina (Sage, 2025)
This two-wave study investigated whether the concurrent and prospective effects of internalizing symptoms and peer status (being liked/disliked) on peer-reported and self-reported victimization were moderated by the classroom prevalence of internalizing symptoms and peer status, respectively, and by classroom size. Multilevel regression analyses were conducted with data collected from 2,641 Finnish secondary school students (Mage = 13.71; 48.8% girls) at the beginning (September 2022) and in the middle of the school year (January 2023). Concurrently, higher levels of internalizing problems and lower status were associated with higher peer-reported and self-reported victimization, but these associations were not moderated by the classroom prevalence of these individual characteristics nor by classroom size. Longitudinally, higher levels of internalizing problems and lower status predicted more self-reported victimization 5 months later, but only lower status predicted higher peer-reported victimization over time. No moderating effect of the classroom features of interest were found.